Analyis of changes in the serum concentration of cystatin c, creatinine and renal neutrophil gelatinase-associated lipocalin in patients with hemorrhagic fever with renal syndrome - E. M. Mingazova; D. A. Valishin; A. Z. Gilmanov; L. R. Shajhullina (Журнал инфектологии)
Introduction. Acute kidney injury is a frequent complication of hemorrhagic fever with renal syndrome. The objective evaluation of аcute kidney injury severity degree is significant in determining the amount of medical actions at hemorrhagic fever with renal syndrome.Objective. Тhe shifts of acute kidney injury biomarkers’ levels (urine neutrophil gelatinase-associated lipocalin, serum cystatin C and serum creatinine) at different periods of hemorrhagic fever with renal syndrome were evaluated.Methods. Depending to hemorrhagic fever with renal syndrome severity the patients were divided into groups with severe (n=16) and moderate form of hemorrhagic fever with renal syndrome (n=10); the control group included 10 healthy individuals. The levels of biomarkers were measured by ELISA.Results. Тhe serum concentration of creatinine and cystatin C – markers of glomerular pathology – increased significantly in hemorrhagic fever with renal syndrome, peaking at oligouric period; while changes of cystatin C were more rapid. Urine neutrophil gelatinase-associated lipocalin level – marker of renal tubular damage – increased 30 to 96 times compared to the control group in fever period of hemorrhagic fever with renal syndrome and gradually decreased thereafter.Conclusion. Тhe use of modern biochemical markers of renal pathology (sCystatin C, urine neutrophil gelatinaseassociated lipocalin) in hemorrhagic fever with renal syndrome, along with traditional indicators, allows a more differentiated approach to the assessment of renal pathology and gives additional evidence to highlight stage and severity of the disease.